g(1,2)*-closed Sets in Bitopological Spaces - K. M. Dharmalingam; A. Thamilisai; O. Ravi (International Journal of Mathematics And its Applications, 2015)
In this paper, we offer a new class of sets called g(1,2)*-closed sets in bitopological spaces and we study some of its basic properties. It turns out that this class lies between the class of τ_1,2-closed sets and the class of (1,2)*-α g-closed sets.